Positive pole piece and secondary battery

By using a multi-layer film structure and a second positive electrode active material with moderate particle size in the positive electrode sheet of the secondary battery, the problem of poor dynamic performance of the conventional battery electrode is solved, and the rate performance and energy density of the battery are improved.

CN119695066APending Publication Date: 2025-03-25安徽得壹能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411894348.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The thick electrodes of traditional secondary batteries have the problem of poor electrode dynamics, which affects the rate performance of the battery.

Method used

The structure of a positive electrode current collector, a first positive electrode film layer, a second positive electrode film layer and a third positive electrode film layer arranged in sequence is adopted, wherein the particle diameter D50 of the second positive electrode active material is smaller than the particle diameter D50 of the first and third positive electrode active materials, thereby improving the porosity and electrolyte adsorption capacity of the second positive electrode film layer.

Benefits of technology

By reducing the concentration polarization between the electrode plates and improving the ionic conductivity, the rate performance of the battery is significantly improved while maintaining excellent energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201336020000091
    Figure BDA0005201336020000091
  • Figure BDA0005201336020000101
    Figure BDA0005201336020000101
  • Figure BDA0005201336020000111
    Figure BDA0005201336020000111
Patent Text Reader

Abstract

The invention discloses a positive pole piece and a secondary battery. The positive pole piece comprises a positive current collector, a first film layer, a second film layer and a third film layer which are sequentially stacked, the first positive electrode film layer comprises a first positive electrode active material; the second positive electrode film layer comprises a second positive electrode active material; the third positive electrode film layer comprises a third positive electrode active material; the particle size D50 of the second positive electrode active material is smaller than the particle size D50 of the first positive electrode active material and smaller than the particle size D50 of the third positive electrode active material. The positive pole piece can improve the dynamic performance of the electrode and improve the rate capability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a positive electrode sheet and a secondary battery. Background Art

[0002] With the widespread use of lithium-ion batteries, consumers have put forward higher requirements for the driving range of electric vehicles. In order to meet higher energy density, most of them improve the energy density of secondary batteries through thick coating and high pressure density. However, while traditional technology improves energy density, it often leads to the problem of poor electrode kinetics of thick electrodes of secondary batteries, which affects the rate performance of the battery. Therefore, it is urgent to improve the kinetics of the electrode and improve the rate performance of the battery. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art to a certain extent. To this end, the present invention provides a positive electrode plate and a secondary battery, which can improve the dynamic performance of the electrode and enhance the battery rate performance.

[0004] Therefore, in a first aspect of the present invention, the present invention provides a positive electrode sheet, comprising: a positive electrode current collector, a first positive electrode film layer, a second positive electrode film layer and a third positive electrode film layer stacked in sequence;

[0005] The first positive electrode film layer includes a first positive electrode active material;

[0006] The second positive electrode film layer includes a second positive electrode active material;

[0007] The third positive electrode film layer includes a third positive electrode active material;

[0008] The particle size D50 of the second positive electrode active material is smaller than the particle size D50 of the first positive electrode active material, and smaller than the particle size D50 of the third positive electrode active material.

[0009] The particle size D50 of the second positive electrode active material is smaller than the particle size D50 of the first positive electrode active material, and smaller than the particle size D50 of the third positive electrode active material. Generally, the smaller the particle size of the active material, the larger the specific surface area. Therefore, the specific surface area of ​​the second positive electrode active material is larger than the specific surface areas of the first and third positive electrode active materials, respectively. The larger the contact area between the second positive electrode active material and the electrolyte, the more conducive it is for the second positive electrode film layer to adsorb more electrolyte, so that the second positive electrode film layer is in an electrolyte-rich state. When the battery cell is charging and discharging, the electrolyte of the second positive electrode film layer can diffuse to the first positive electrode film layer and the third positive electrode film layer, reducing the concentration polarization between the pole pieces and improving their kinetic performance. In addition, the particle size D50 of the second positive electrode active material is smaller, so that the pole piece porosity of the second positive electrode film layer is higher than that of the first and third positive electrode film layers, respectively. The porosity of the second positive electrode film layer is increased, and the electrolyte is more fully infiltrated, which can improve the ionic conductivity, thereby improving the problems of electrolyte infiltration and ion diffusion. As a result, the rate performance of the battery can be improved.

[0010] In some embodiments, the ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the first positive electrode active material is 0.2 to 0.8, preferably 0.4 to 0.6.

[0011] In some embodiments, the ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the third positive electrode active material is 0.2 to 0.8, preferably 0.4 to 0.6.

[0012] In some embodiments, the total thickness of the first positive electrode film layer, the second positive electrode film layer and the third positive electrode film layer is 100-400 μm.

[0013] In some embodiments, the ratio of the thickness of the second positive electrode film layer to the total thickness is 0.1 to 0.5, preferably 0.2 to 0.4.

[0014] In some embodiments, the thickness of the first positive electrode film layer is 30-100 μm.

[0015] In some embodiments, the thickness of the third positive electrode film layer is 30-100 μm.

[0016] In some embodiments, the particle size D50 of the second positive electrode active material is 0.4-10 μm.

[0017] In a second aspect of the present invention, the present invention provides an ion battery, comprising the positive electrode sheet of the first aspect, so that the ion battery has excellent energy density and rate performance.

[0018] Compared with the prior art, the present invention has the following beneficial technical effects:

[0019] (1) The ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the first positive electrode active material of the present invention is 0.2 to 0.8, and the ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the third positive electrode active material is 0.2 to 0.8. This increases the porosity of the second positive electrode film layer, allows for more complete electrolyte infiltration, reduces concentration polarization between pole pieces, increases ionic conductivity, and thus improves battery rate performance.

[0020] (2) The ratio of the thickness of the second positive electrode film layer to the total thickness of the present invention is 0.1 to 0.5, which not only increases the porosity of the second positive electrode film layer and improves the dynamic performance of the battery, but also maintains a good energy density.

[0021] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0023] Figure 1 A schematic cross-sectional view of a positive electrode sheet of the present invention;

[0024] Among them, A is the current collector, L1 is the first positive electrode film layer, L2 is the second positive electrode film layer, and L3 is the third positive electrode film layer. DETAILED DESCRIPTION

[0025] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.

[0026] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.

[0027] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0028] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.

[0029] In a first aspect of an embodiment of the present invention, the present invention provides a positive electrode sheet, comprising: a positive electrode current collector, a first positive electrode film layer, a second positive electrode film layer and a third positive electrode film layer stacked in sequence;

[0030] The first positive electrode film layer includes a first positive electrode active material;

[0031] The second positive electrode film layer includes a second positive electrode active material;

[0032] The third positive electrode film layer includes a third positive electrode active material;

[0033] The particle size D50 of the second positive electrode active material is smaller than the particle size D50 of the first positive electrode active material, and smaller than the particle size D50 of the third positive electrode active material.

[0034] The particle size D50 of the second positive electrode active material is smaller than the particle size D50 of the first positive electrode active material, and smaller than the particle size D50 of the third positive electrode active material. Generally, the smaller the particle size of the active material, the larger the specific surface area. Therefore, the specific surface area of ​​the second positive electrode active material is larger than the specific surface areas of the first and third positive electrode active materials, respectively. The larger the contact area between the second positive electrode active material and the electrolyte, the more conducive it is for the second positive electrode film layer to adsorb more electrolyte, so that the second positive electrode film layer is in an electrolyte-rich state. When the battery cell is charging and discharging, the electrolyte of the second positive electrode film layer can diffuse to the first positive electrode film layer and the third positive electrode film layer, reducing the concentration polarization between the pole pieces and improving their kinetic performance. In addition, the particle size D50 of the second positive electrode active material is smaller, so that the pole piece porosity of the second positive electrode film layer is higher than that of the first and third positive electrode film layers, respectively. The porosity of the second positive electrode film layer is increased, and the electrolyte is more fully infiltrated, which can improve the ionic conductivity, thereby improving the problems of electrolyte infiltration and ion diffusion. As a result, the rate performance of the battery can be improved.

[0035] In some embodiments of the present invention, the ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the first positive electrode active material is 0.2 to 0.8, preferably 0.4 to 0.6.

[0036] When the ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the first positive electrode active material is 0.2 to 0.8, the second positive electrode film layer has sufficient porosity to absorb the electrolyte, and at the same time, the porosity is significantly different from that of the first positive electrode film layer. The electrolyte absorbed by the second positive electrode film layer can diffuse to the first positive electrode film layer, reducing the concentration polarization between the pole pieces. Thus, the kinetic performance is improved while maintaining excellent energy density.

[0037] As an example, the ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the first positive electrode active material is 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, etc.

[0038] In some embodiments of the present invention, the ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the third positive electrode active material is 0.2 to 0.8, preferably 0.4 to 0.6.

[0039] When the ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the third positive electrode active material is 0.2 to 0.8, the second positive electrode film layer has sufficient porosity to absorb the electrolyte, and at the same time, the porosity is significantly different from that of the third positive electrode film layer. The electrolyte absorbed by the second positive electrode film layer can diffuse to the third positive electrode film layer, reducing the concentration polarization between the pole pieces, improving the electrode wettability, and enhancing its kinetic performance while maintaining excellent energy density. As a result, the battery rate performance can be improved.

[0040] As an example, the ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the third positive electrode active material is 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, etc.

[0041] In some embodiments of the present invention, the total thickness of the first positive electrode film layer, the second positive electrode film layer and the third positive electrode film layer is 100-400 μm, and further, the total thickness is 140-200 μm, thereby improving the battery rate performance.

[0042] As an example, the total thickness is 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, etc.

[0043] In some embodiments of the present invention, the ratio of the thickness of the second positive electrode film layer to the total thickness is 0.1 to 0.5, preferably 0.2 to 0.4.

[0044] The thickness of the second positive electrode film layer has an important influence on the dynamics and overall energy density of the battery. When the ratio of the thickness of the second positive electrode film layer to the total thickness is 0.1 to 0.5, the thickness is optimal, which can not only increase the porosity of the second positive electrode film layer, improve the liquid absorption capacity, thereby improving the dynamic performance, but also meet the energy density required by the battery. Thus, the battery rate performance is improved.

[0045] As an example, the ratio of the thickness of the second positive electrode film layer to the total thickness is 0.1, 0.2, 0.3, 0.4, 0.5, etc.

[0046] In some embodiments of the present invention, the thickness of the first positive electrode film layer is 30-100 μm, thereby further improving the battery rate performance.

[0047] As an example, the thickness of the first positive electrode film layer is 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, etc.

[0048] In some embodiments of the present invention, the thickness of the third positive electrode film layer is 30-100 μm, thereby improving the battery rate performance.

[0049] As an example, the thickness of the third positive electrode film layer is 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, etc.

[0050] In some embodiments of the present invention, the particle size D50 of the second positive electrode active material is 0.4-10 μm, preferably 0.8-1.9 μm.

[0051] The particle size of the active material is closely related to the porosity. When the particle size D50 of the second positive electrode active material is 0.4 to 10 μm, the second positive electrode film layer has excellent porosity, which improves its ability to adsorb electrolyte. The electrolyte adsorbed by the second positive electrode film layer can diffuse to the first and third positive electrode film layers, improving the concentration polarization of the first and third positive electrode film layers during charging and discharging. Therefore, the positive electrode plate of the present invention improves the energy density while ensuring the dynamic performance.

[0052] As an example, the particle size D50 of the second positive electrode active material is 0.4 μm, 1.4 μm, 2.4 μm, 3.4 μm, 4.4 μm, 5.4 μm, 6.4 μm, 7.4 μm, 8.4 μm, 9.4 μm, 10 μm, etc.

[0053] In a second aspect of the embodiments of the present invention, the present invention provides an ion battery, comprising the positive electrode sheet of the first aspect, so that the ion battery has excellent energy density and rate performance.

[0054] In some embodiments of the present invention, the positive electrode current collector includes a metal foil or a composite current collector. For example, the metal foil can be aluminum foil. The composite current collector includes a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).

[0055] In some embodiments of the present invention, the first positive electrode active material, the second positive electrode active material and the third positive electrode active material include at least one of an olivine-structured lithium-containing phosphate, a lithium transition metal oxide and their respective modified compounds.

[0056] As examples, lithium transition metal oxides include, but are not limited to, lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, referred to as NCM333, LiNi 0.5 Co 0.2 Mn 0.3 O2, referred to as NCM523, LiNi 0.5 Co 0.25 Mn 0.25 O2, referred to as NCM211, LiNi 0.6 Co 0.2 Mn 0.2 O2, referred to as NCM622, LiNi 0.8 Co 0.1 Mn 0.1 O2, referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and at least one of its modified compounds.

[0057] As an example, the olivine-structured lithium-containing phosphate includes but is not limited to at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0058] In some embodiments of the present invention, the ion battery further comprises a negative electrode plate, and the negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer. The negative electrode current collector may be copper foil. The negative electrode active material comprises at least one of graphite, soft carbon, hard carbon, and silicon-based materials.

[0059] In some embodiments of the present invention, the first positive electrode film layer, the second positive electrode film layer and the third positive electrode film layer further include a binder. The binder includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluoroethylene-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.

[0060] In some embodiments of the present invention, the first positive electrode film layer, the second positive electrode film layer and the third positive electrode film layer further include a conductive agent, which includes at least one of carbon black SP, KS-6, KS-15, Ketjen black, single-walled carbon tubes, multi-walled carbon nanotubes and graphene.

[0061] In some embodiments of the present invention, the battery further comprises an electrolyte, and the electrolyte comprises a solvent, a lithium salt and a functional additive. The solvent comprises at least one of ethylene carbonate, ethylene carbonate, polycarbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, ethyl acetate and ethyl propionate; the lithium salt comprises at least one of lithium hexafluorophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium bisoxalate borate, lithium difluorooxalate borate and lithium difluorobisoxalate phosphate; the additive comprises at least one of lithium dioxalate borate, lithium difluorooxalate borate, lithium tetrafluorooxalate phosphate, 1,3-propane sultone, ethylene sulfate, ethylene carbonate, propylene sulfite, 1,4-butane sultone, tris(trimethylsilane) phosphate, tris(trimethylsilane) phosphite, fluoroethylene carbonate, vinylene carbonate, fluoroethylene carbonate and lithium difluorophosphate.

[0062] In some embodiments of the present invention, the battery further includes a separator, and the separator includes at least one of polyethylene, polypropylene, non-woven fabric, and a composite separator.

[0063] In some embodiments of the present invention, a method for preparing a battery includes:

[0064] S1000. Preparation of the first positive electrode film layer.

[0065] The lithium iron phosphate, conductive carbon black, binder (PVDF) and solvent n-methylpyrrolidone (NMP) are mixed and stirred uniformly to obtain a first slurry, and the first slurry is uniformly coated on an aluminum foil current collector and then dried at high temperature.

[0066] S2000. Preparation of the second positive electrode film layer.

[0067] The lithium iron phosphate, conductive carbon black, binder (PVDF) and solvent n-methylpyrrolidone (NMP) are mixed and stirred evenly to obtain a second slurry, and the second slurry is evenly coated on the dried first film layer film, and then dried at high temperature.

[0068] S3000. Preparation of the third positive electrode film layer.

[0069] The lithium iron phosphate, conductive carbon black, binder (PVDF) and solvent n-methylpyrrolidone (NMP) are mixed and stirred evenly to obtain a third slurry, and the third slurry is evenly coated on the dried second film layer film, and then dried at high temperature.

[0070] S4000.Cold pressing

[0071] After the membrane is cold pressed, the positive electrode sheet can be obtained ( Figure 1 ).

[0072] S5000.Battery assembly

[0073] The positive electrode sheet, the separator and the negative electrode sheet are stacked, then hot pressed, welded and put into a shell to make a dry cell, which is then baked. The electrolyte is injected, and other processes such as formation and aging are performed to obtain a battery.

[0074] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0075] Embodiment 1:

[0076] 1. Preparation of positive electrode

[0077] (1) Preparation of the first positive electrode film layer: lithium iron phosphate (the particle size of the first positive electrode active material is D10: 0.3 μm, D50: 1.1 μm, and D90: 3.5 μm), conductive carbon black, a binder (PVDF), and a solvent n-methylpyrrolidone (NMP) are mixed and stirred at a weight ratio of 95:2:3:80 to obtain a first slurry, and the first slurry is evenly coated on a 13 μm aluminum foil current collector to control the thickness of the first positive electrode film layer to 50 μm, and then dried at 110°C.

[0078] (2) Preparation of the second positive electrode film layer: lithium iron phosphate (the particle size of the second positive electrode active material is D10 0.1 μm, D50 0.5 μm, and D90 1.5 μm), conductive carbon black, binder (PVDF) and solvent n-methylpyrrolidone (NMP) are mixed and stirred at a weight ratio of 95:2:3:80 to obtain a second slurry, and the second slurry is evenly coated on the dried first film layer film to control the thickness of the second positive electrode film layer to be 50 μm. Then, the film is dried at 110°C.

[0079] (3) Preparation of the third positive electrode film layer: lithium iron phosphate (the particle size of the third positive electrode active material is D10: 0.3 μm, D50: 1.1 μm, and D90: 3.5 μm), conductive carbon black, a binder (PVDF) and a solvent n-methylpyrrolidone (NMP) are mixed and stirred evenly to obtain a third slurry, and the third slurry is evenly coated on the dried second film layer diaphragm to control the thickness of the third positive electrode film layer to 50 μm, and then dried at 110°C.

[0080] (4) Cold pressing treatment: After the membrane is subjected to cold pressing treatment, a positive electrode sheet with a total thickness of 150 μm can be obtained.

[0081] 2. Secondary Battery Preparation

[0082] (1) Preparation of negative electrode sheet: artificial graphite, conductive carbon black, carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR) and water were mixed in a mass ratio of 95:2:1:2:100 and stirred evenly to obtain negative electrode slurry. The negative electrode current collector was made of 6μm copper foil, which was matched with the above positive electrode sheet according to the NP ratio of 1.13, and the negative electrode roller compaction density was uniformly 1.6g / CC.

[0083] (2) Preparation of electrolyte: Ethylene carbonate (EC), polycarbonate (PC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 1:1:1, and lithium hexafluorophosphate (LiPF6) was added to prepare an electrolyte containing 1.1 M lithium hexafluorophosphate (LiPF6).

[0084] (3) Preparation of isolation membrane: A 2 μm ceramic coating is added to a 7 μm polyethylene film (PE), and then a 3 μm adhesive layer is applied to obtain a battery isolation membrane.

[0085] (4) Preparation of secondary batteries: The positive electrode sheet, negative electrode sheet and isolation film obtained by the above preparation method are wound to obtain a bare battery cell, which is placed in an outer packaging aluminum shell, and the above electrolyte is added. After packaging, infiltration, formation, aging, capacity division and other processes, a secondary battery is obtained.

[0086] The porosity ε of the entire electrode is tested according to the following method.

[0087] During the preparation of the electrode sheet, take the positive electrode sheet coated with the third active material layer and use a punching machine to punch out an area of ​​0.154 cm 2 Select 20 small discs with good appearance and no powder falling off the edges and put them into the sample cup. Record the number of samples A and calculate the apparent volume V1. Place the sample cup with the sample in the electrolyte, and the increase in the weight of the electrode is recorded as W, so as to obtain the porosity of the sample to be tested. Porosity ε=W / ρ / V1, where the apparent volume V1=S*H*A, where: S is the area of ​​the small disc, unit is cm 2 ; H is the sample thickness, in cm; A is the number of samples, in Pcs; W is the electrolyte absorption, in g; V1 is the apparent volume of the sample, in cm 3 , ρ is the electrolyte density, in g / mL.

[0088] Embodiment 2:

[0089] The difference between Example 2 and Example 1: In Example 2, the thickness of the first positive electrode film layer is 67 μm, the thickness of the second positive electrode film layer is 66 μm, the thickness of the third positive electrode film layer is 67 μm, and the total thickness of the positive electrode sheet is 200 μm.

[0090] Embodiment 3:

[0091] The difference between Example 3 and Example 1: In Example 3, the thickness of the first positive electrode film layer is 83 μm, the thickness of the second positive electrode film layer is 84 μm, the thickness of the third positive electrode film layer is 83 μm, and the total thickness of the positive electrode sheet is 250 μm.

[0092] Embodiment 4:

[0093] The difference between Example 4 and Example 1: In Example 3, the thickness of the first positive electrode film layer is 100 μm, the thickness of the second positive electrode film layer is 100 μm, the thickness of the third positive electrode film layer is 100 μm, and the total thickness of the positive electrode sheet is 300 μm.

[0094] Embodiment 5:

[0095] The difference between Example 5 and Example 2 is that in Example 5, the ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the first and third positive electrode active materials is 0.2.

[0096] Embodiment 6:

[0097] The difference between Example 6 and Example 5 is that in Example 6, the ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the first and third positive electrode active materials is 0.3.

[0098] Embodiment 7:

[0099] The difference between Example 7 and Example 6 is that in Example 7, the ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the first and third positive electrode active materials is 0.4.

[0100] Embodiment 8:

[0101] The difference between Example 8 and Example 7 is that in Example 8, the ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the first and third positive electrode active materials is 0.6.

[0102] Embodiment 9:

[0103] The difference between Example 9 and Example 8 is that in Example 9, the ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the first and third positive electrode active materials is 0.7.

[0104] Embodiment 10:

[0105] The difference between Example 10 and Example 9 is that in Example 10, the ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the first and third positive electrode active materials is 0.8.

[0106] Embodiment 11:

[0107] The difference between Example 11 and Example 2 is as follows: in Example 11, the thickness of the first positive electrode film layer is 90 μm, the thickness of the second positive electrode film layer is 20 μm, and the thickness of the third positive electrode film layer is 90 μm.

[0108] Embodiment 12:

[0109] The difference between Example 12 and Example 11: In Example 12, the thickness of the first positive electrode film layer is 80 μm, the thickness of the second positive electrode film layer is 40 μm, and the thickness of the third positive electrode film layer is 80 μm.

[0110] Embodiment 13:

[0111] The difference between Example 13 and Example 12 is as follows: in Example 11, the thickness of the first positive electrode film layer is 60 μm, the thickness of the second positive electrode film layer is 80 μm, and the thickness of the third positive electrode film layer is 60 μm.

[0112] Embodiment 14:

[0113] The difference between Example 14 and Example 13: In Example 14, the thickness of the first positive electrode film layer is 50 μm, the thickness of the second positive electrode film layer is 100 μm, and the thickness of the third positive electrode film layer is 50 μm.

[0114] Comparative Example 1:

[0115] The difference between Comparative Example 1 and Example 1 is as follows: in Comparative Example 1, the thickness of the first positive electrode film layer is 100 μm, the thickness of the third positive electrode film layer is 100 μm, there is no second positive electrode film layer, and the total thickness of the positive electrode sheet is 200 μm.

[0116] The preparation parameters of the positive electrode sheets of the above embodiments and comparative examples are recorded in Table 1.

[0117] Table 1 Preparation parameters of positive electrode sheets of various embodiments and comparative examples

[0118]

[0119] Battery performance test

[0120] 1. Battery mass energy density test:

[0121] The mass M of the batteries produced in the above embodiments and comparative examples is measured respectively, in kg. Battery energy calibration: After the batteries are left at room temperature for 2 hours, each battery is charged to 3.65V at a current of 0.33C, constant voltage to 0.05C, and then discharged to 2V at a rate of 0.33C. The discharge energy E0 is measured in Wh, and the mass energy density of the battery = E0 / M.

[0122] 2. Battery discharge rate performance test:

[0123] Two secondary batteries were taken from each group in each of the above embodiments and comparative examples for parallel testing. After the battery was left to stand at room temperature for 2 hours, each battery was charged to 3.65V at a current of 0.33C, constant voltage to 0.05C, and then discharged to 2V at a rate of 0.33C to obtain the discharge energy E0. Then each battery was charged at a rate of 0.33C at room temperature to a voltage of 4.25V, and then discharged at a rate of 2C to a voltage of 2.0V, and the energy measured was E1. The rate performance energy retention rate calculation formula is: rate performance = E1 / E0×100%. The larger the energy retention rate, the better the ion diffusion kinetics of the secondary battery, and the stronger the ion diffusion capacity at a large rate.

[0124] 3. Charging DC internal resistance test:

[0125] Two secondary batteries were taken from each group in each of the above embodiments and comparative examples for parallel testing. After the battery was left at room temperature for 2 hours, each battery was charged to 3.65V at 0.33C current, constant voltage to 0.05C, and then discharged to 50% SOC at 0.33C rate. After standing for 1 hour, the voltage after standing was recorded as OCV1, and charged at 2C rate for 10 seconds, and the voltage after charging for 10 seconds was recorded as OCV2; the charging DC internal resistance (DCR) of the battery at 50% SOC at room temperature was obtained as (OCV2-OCV1) / 2C current, and the unit of charging DC internal resistance was mΩ. The smaller the charging DCR, the better the ion diffusion kinetics of the secondary battery and the stronger the charging capacity.

[0126] Test results:

[0127] The secondary battery performance test results of all embodiments and comparative examples are shown in Table 2.

[0128] Table 2 Secondary battery performance test results of all embodiments and comparative examples

[0129]

[0130]

[0131] From the comparison of the comparative examples and the embodiments in Tables 1 and 2, it can be seen that the overall performance of the battery in Comparative Example 1 is poor due to the lack of the second positive electrode film layer. The battery weight energy density, charging DC internal resistance and discharge rate performance of Embodiments 1-14 are better than those of Comparative Example 1, and the overall performance of the batteries of Embodiments 1-14 is significantly improved.

[0132] It can be seen from Examples 1-4 that when the particle size D50 of the second positive electrode active material and the ratio of the second positive electrode film layer thickness to the total thickness remain unchanged, the thickness of each positive electrode film layer increases, the total thickness of the electrode sheet increases, and the total amount of active material increases, so the weight energy density gradually increases, but the porosity of the electrode sheet gradually decreases, resulting in the electrolyte's wettability to the electrode material to deteriorate, which to a certain extent affects the mobility of lithium ions and the electrochemical properties of the battery, so the charging DC internal resistance increases and the discharge rate performance decreases.

[0133] It can be seen from Examples 5-10 that, when the total thickness of each positive electrode film layer and the electrode sheet remains unchanged, the particle size D50 of the second positive electrode active material increases, which improves the weight energy density of the battery, but reduces the porosity of the electrode sheet, affecting the infiltration of the electrolyte and the migration of ions, resulting in an increase in the battery charging DC internal resistance and a decrease in the discharge rate performance.

[0134] It can be seen from Examples 11-14 that when the particle size D50 of the second positive electrode active material and the total thickness of the electrode sheet remain unchanged, the thickness of the second positive electrode film layer increases. Although the weight energy density of the battery is reduced, the porosity of the electrode sheet is increased, and its ability to adsorb electrolyte is improved, so that the electrolyte can fully infiltrate the electrode material. At the same time, the electrolyte adsorbed by the second positive electrode film layer can diffuse to the first and third positive electrode film layers, which improves the concentration polarization of the first and third positive electrode film layers during charging and discharging, reduces the DC internal resistance of the battery charging, and improves the discharge rate performance.

[0135] It can be seen from this that the positive electrode plate of the present invention, by setting three layers of positive electrode film layers and by regulating the particle size D50 of the second positive electrode film layer and the thickness ratio of the second positive electrode film layer, better balances the relationship between porosity and energy density, thereby improving the ion diffusion kinetics of the electrode and improving the battery rate performance.

[0136] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0137] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A positive electrode sheet, characterized in that: include: A positive electrode current collector, a first positive electrode film layer, a second positive electrode film layer and a third positive electrode film layer are stacked in sequence; The first positive electrode film layer includes a first positive electrode active material; The second positive electrode film layer includes a second positive electrode active material; The third positive electrode film layer includes a third positive electrode active material; The particle size D50 of the second positive electrode active material is smaller than the particle size D50 of the first positive electrode active material, and smaller than the particle size D50 of the third positive electrode active material.

2. The positive electrode sheet according to claim 1, characterized in that: The ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the first positive electrode active material is 0.2 to 0.8, preferably 0.4 to 0.

6.

3. The positive electrode sheet according to claim 1, characterized in that: The ratio of the particle size D50 of the second positive electrode active material to the particle size D50 of the third positive electrode active material is 0.2 to 0.8, preferably 0.4 to 0.

6.

4. The positive electrode sheet according to claim 1, characterized in that: The total thickness of the first positive electrode film layer, the second positive electrode film layer and the third positive electrode film layer is 100-400 μm.

5. The positive electrode sheet according to claim 4, characterized in that: The ratio of the thickness of the second positive electrode film layer to the total thickness is 0.1 to 0.5, preferably 0.2 to 0.

4.

6. The positive electrode sheet according to claim 1 or 4, characterized in that: The thickness of the first positive electrode film layer is 30-100 μm.

7. The positive electrode sheet according to claim 1 or 4, characterized in that: The thickness of the third positive electrode film layer is 30-100 μm.

8. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The particle size D50 of the second positive electrode active material is 0.4 to 10 μm.

9. A secondary battery, characterized in that: A positive electrode sheet comprising the positive electrode sheet according to any one of claims 1 to 8.